Insider Trading In Share Trading: An Analysis of Fraud And The Abuse of Informational Advantage From The Perspectives of Capital Market Law and Competition Law In Indonesia - Angga Faridi Algamar; Moh Ramadhan Wibisono; Masagus M. Ezar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of capital markets requires the presence of transparency, fairness, and equality among all market participants. However, the practice of insider trading remains a significant issue that can undermine market integrity. Insider trading refers to the use of material non-public information by certain parties to gain an advantage in stock trading. This practice not only violates the principle of information disclosure but also creates information asymmetry that may distort market mechanisms. This study aims to analyze the forms and characteristics of insider trading as a fraudulent practice and misuse of informational advantage, as well as to assess the relevance of competition law principles in identifying distortions of fairness and equality within the market. The research employs a normative juridical method with statutory and conceptual approaches, utilizing primary legal materials such as Law Number 8 of 1995 concerning Capital Markets and Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The findings indicate that insider trading constitutes a form of fraud based on the misuse of informational advantage, which leads to inequity in the market. Although it does not legally qualify as a monopolistic practice, insider trading still creates distortions in the principles of fair competition.